POLITENESS IN DOMESTIC VERBAL VIOLENCE AGAINST WOMEN IN INDONESIA - Ike Revita; Rovika Triclarise; Nila Anggraini; Fahmi Gunawan (Aksara, 2020)
Kesantunan berbahasa tidak hanya terjadi di dalam situasi resmi, normal, dan dalam komunikasi yang baik, tetapi juga dalam situasi tidak resmi, tidak normal, dan penutur dalam keadaan marah. Penelitian ini bertujuan untuk membahas bentuk kesantunan berbahasa seseorang yang sedang marah. Data diperoleh di Sumatera Barat. Data dikumpulkan melalui mencatat, merekam, dan melakukan wawancara. Analisis data menggunakan konsep kesantunan dan kekerasan verbal terhadap wanita. Hasil temuan dianalisis secara deskriptif yang ditambahi dengan beberapa tabel untuk menyajikan data tertentu. Hasil temuan menunjukkan bahwa ada empat bentuk kesantunan di dalam kekerasan verbal domestik terhadap wanita, yaitu permintaan, penolakan, janji, dan ekpresif. Kesantunan dalam bentuk permintaan menjadi pola yang dominan, yaitu 37%. Hal demikian terjadi karena penutur menginginkan wanita atau istrinya melakukan apa yang mereka minta.Kata kunci: kesantunan, kekerasan verbal, wanita, pragmatik, IndonesiaPoliteness happens in good situations not only in regular dan formal conversations with the speaker, but also in non-formal and irregular conversation, and the speaker is in a bad situation. This article is, then,  aimed at describing the forms of the politeness of the speakers who are in anger. The objective of the study is to identify the forms politeness in that verbal violence. The data were taken in Sumatera Barat. To obtain the data, the observational method with note-taking, recording, and interviewing was conducted. Fifteen women were being interviewed, and thirteen men (husband) from Sumatera Barat.  The data were analyzed by using the concept of politeness (Oktavianus Revita, 2013) and verbal violence against women (Cantwell, Farzanegan, Khan, 2000). The result of the analysis is descriptively done in which some tables and charts were used to display the number of the occurrence of certain data. The percentage was also used. The findings pointed out that there were four forms of politeness in domestic verbal violence. They are politeness of 1) request; 2) refusal; 3) promise; and 4) expressiveness. Politeness of requests occurs most dominantly because the speakers wanted these women to do what they expected.